Gender Asymmetry and Mutual Sexual Relations in Online Legal Interpretation - Farhana Ismail; Fatima Seedat (African Journal of Gender and Religion (AJGR))
As part of a larger research project which examines Muslim women’s sexual and reproductive health rights within the interlocutory space of online fatwas, this paper provides a glimpse into the co-construction, by muftis and petitioners, of an Islamic discourse of jurisprudence on sexuality in marriage. This paper argues that the discourse moves away from the dominant legal one of male sexual right and female responsibility to fulfil, towards an underlying and more subtle ethical discourse centred on mutuality. Combining a methodology of feminist post-structural discourse analysis with a legal interpretive framework drawn from classical legal methodologies, the paper analyses a fatwa by South African-based Deoband mufti Ebrahim Desai on his online fatwa platform askimam.org. Assessed alongside ancillary fatwas on his website, the analysis reveals how petitioners and muftis remain committed to the gender asymmetric legal (fiqh) ) rules governing Muslim marriage, yet also articulate views based on expectations of reciprocity and mutuality in sexual relations prevalent in contemporary marriage. Where some petitioners grapple with the dissonance created by their pietistic loyalty to the gender asymmetric legal tradition and ethical expectations of reciprocity and mutuality, muftis such as Desai respond by employing discernible strategies that produce a discourse of mutuality in sexual relations within modern marriage. This paper asserts that both petitioners and muftis in online fatwas like those of askimam.org, have the potential to reformulate and reconfigure present and future fiqh discourses on sexuality within Muslim marriage. This is evident in their alignment with an ethics of marriage and well being, located in ideals of reciprocity and mutuality.